Hubungan Antara Subjective Well-Being Dengan Kepuasan Kerja Guru Honorer - Lufiana, Ozie Herfin, Achmad Dwityanto, S.Psi, M.Si (2017)
more community who want work, where job satisfaction is the individual. Where there is one of the psychological factors namely the welfare of the individual and the welfare of the individual is located in subjective well-being, if subjective well-being noted and will improve job satisfaction on the individual. The purpose of this research is to know the relationship between the subjective well-being with job satisfaction, and to know the subjective well-being with job satisfaction. The method used is the quantitative approach. The subject of the research that is used is temporary teachers se counties.Ngawi, which amounted to 80 people. Sampling techniques used is purposive sampling. That is used to measure the scale of subjective well-being and job satisfaction scale is performed using analysis methods.technique of non-parametrik correlation with the help of (SPSS Statistical Product and Service Solution) 16.0 for Windows Program. Based on the results of the data analysis, then the obtained correlation coefficient rxy = 0,668; with sig. 0,000; (p < 0.01). So the hypothesis that proposed accepted, it can be said there is a very significant positive relationship between subjective well-being with job satisfaction teachers. Effective contribution subjective well-being with job satisfaction of 44.6% and and there are still 55,4% other factors that affect job satisfaction. Key Words: job satisfaction, Subjective well-being, teachers, temporary.